Pelaksanaan Metode Hypnoteaching Berbantuan Media Gambar Pada Mata Pelajaran Sejarah Kelas X IPS SMA N 1 Sitiung - Sisil Veronika Anggela; Zulfa; Ranti Nazmi (Program Studi Pendidikan Sejarah Universitas Riau, 2023)
This thesis examines the implementation of the hypnoteaching method assisted by media images in history class X IPS SMA N 1 Sitiung. The implementation of the hypnoteaching method assisted by media images in the history subject of class X IPS is carried out to increase students' interest in learning history. This writing aims to describe the implementation of the hypnoteaching method assisted by media images in the history subject of class X IPS SMA N 1 Sitiung. This research method is quantitative using a descriptive approach. Data collection is through questionnaires, interviews, and documentation. Questionnaires were distributed to students in class X, totaling 30 people. The data analysis technique is through the data collection stage, through descriptive analysis techniques using the percentage formula and after that conclusions are drawn. The results of this study indicate that the implementation of the Haypotiching method assisted by media images in history subjects at SMA N 1 can create an effective and enjoyable teaching and learning process and is able to provide meaning for students so that the material provided by the teacher can be well received and stays in students' memories.